Pilot Evaluation of Two Fasciola hepatica Biomarkers for Supporting Triclabendazole (TCBZ) Efficacy Diagnostics - Collett, Clare F. (Molecules, 2020)
Fasciola hepatica, the causative agent of fasciolosis, is a global threat to public health, animal welfare, agricultural productivity, and food security. In the ongoing absence of a commercial vaccine, independent emergences of anthelmintic-resistant parasite populations worldwide are threatening the sustainability of the few flukicides presently available, and particularly triclabendazole (TCBZ) as the drug of choice. Consequently, prognoses for future fasciolosis control and sustained TCBZ application necessitate improvements in diagnostic tools to identify anthelmintic efficacy. Previously, we have shown that proteomic fingerprinting of F. hepatica excretory/secretory (ES) products offered new biomarkers associated with in vitro TCBZ-sulfoxide (SO) recovery or death. In the current paper, two of these biomarkers (calreticulin (CRT) and triose phosphate isomerase (TPI)) were recombinantly expressed and evaluated to measure TCBZ efficacy via a novel approach to decipher fluke molecular phenotypes independently of molecular parasite resistance mechanism(s), which are still not fully characterised or understood. Our findings confirmed the immunoreactivity and diagnostic potential of the present target antigens by sera from TCBZ-susceptible (TCBZ-S) and TCBZ-resistant (TCBZ-R) F. hepatica experimentally infected sheep.